2004
DOI: 10.1097/01.aids.0000131385.60974.b9
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated liposomal doxorubicin plus highly active antiretroviral therapy versus highly active antiretroviral therapy alone in HIV patients with Kaposi's sarcoma

Abstract: Twenty-eight HIV patients either naive or failing highly active antiretroviral therapy (HAART)with moderate-advanced Kaposi's sarcoma (KS)were randomly chosen to initiate a new HAART regimen plus pegylated liposomal doxorubicin(PLD) or the new HAART regimen alone. After 48 weeks, better response rates were observed in the HAART plus PLD group (76% versus 20%). In HIV-infected patients with moderate-advanced KS, HAART alone may not be enough for KS response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 9 publications
2
89
0
2
Order By: Relevance
“…A high incidence of secondary malignancies with PLD use was also noted by Martin-Carbonero et al [9] in reviewing the long-term results of PLD treatment for patients with Kaposi's sarcoma: of the 29 deaths in that series, nine were a result of malignant disease. Seven deaths were a result of lymphoma, a known association because all patients were HIV ϩ .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…A high incidence of secondary malignancies with PLD use was also noted by Martin-Carbonero et al [9] in reviewing the long-term results of PLD treatment for patients with Kaposi's sarcoma: of the 29 deaths in that series, nine were a result of malignant disease. Seven deaths were a result of lymphoma, a known association because all patients were HIV ϩ .…”
Section: Discussionmentioning
confidence: 54%
“…The associated lower incidence of cardiotoxicity [8] makes it an attractive option for the treatment of patients with various malignancies that are considered sensitive to anthracyclines. PLD is approved for use in patients with Kaposi sarcoma [9], platinum-resistant recurrent ovarian cancer [10], and multiple myeloma. Recently, the combination of carboplatin and PLD was shown to lead to a longer progression-free survival interval in patients with platinum-sensitive recurrences, when compared with carboplatin and paclitaxel [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged administration has shown a good safety profile [1][2][3]. Recently, concerns of a higher risk for oral cavity squamous cell carcinoma in patients with a history of prolonged exposure to PLD was reported [4,5].…”
mentioning
confidence: 99%
“…Even though there has been an increasing incidence of non-AIDS-defining malignancies in the post-highly active antiretroviral therapy era, the incidence of cancers of the oral cavity in HIV patients is Ͻ1% [9]. Treatment of HIV-related Kaposi's sarcoma with PLD has been associated with squamous cell carcinoma of the tongue [2]. It was reported that three of 16 patients with ovarian cancer who were exposed to long-term PLD for a period Ն3 years developed oral cavity malignancies and one patient developed sublingual mucosal high-grade dysplasia [4,5].…”
mentioning
confidence: 99%